Natality rate of cows and development of calves submitted to early weaning in the Pantanal region, Brazil - Catto, João Batista; Afonso, Euripedes (Pesquisa Agropecuaria Brasileira, 2001)
The effect of early weaning on the natality rate of Nelore cows in native pasture was evaluated during one reproductive breeding period. The calves from seventy-nine multiparous and primiparous cows were weaned at 4th to 6th month and supplemented (group A) or at 7th to 9th month and nonsupplemented (group B). Natality rate was greater in group A (81.5%) than in group B (13.1%) (P < 0.001). There was no difference in the natality rate between multiparous and primiparous cows in group A (80.9 and 82.3%) or B (18.1 and 6.2%), respectively (P > 0.58). At the end of the dry season calves from group A weighed 5.4 kg less than calves from group B (P < 0.009).